Penafsiran Tentang Jilbab dalam Pandangan K.H. M. Quraish Shihab - Siti Mu’awiyah Roni (Universitas Islam Malang, 2022)
This study aims to determine the views of KH M Quraish Shihab about the hijab. The problem obtained is the question of M. Quraish shihab's opinion in interpreting Surat al-Ahzab and Surah An-Nur regarding the law of wearing the hijab. In Surah Al-Ahzab and An-Nur M. Quraish Shihab interprets that the law of wearing the hijab for women is not a must or an obligation. In this case we are also not allowed to say that a woman who covers her entire body except for her face and palms, has carried out the command and the sound of the verse above, but we also cannot say that a woman who does not wear a veil or shows part of her hands, that the woman has definitely violates religious instructions, because according to Quraish Shihab not all the commands listed in the Qur'an are mandatory commands, but they mean suggestions and prohibitions but the point is that they should be abandoned